1996
DOI: 10.1210/endo.137.12.8940403
|View full text |Cite
|
Sign up to set email alerts
|

In vivo regulation of peripheral-type benzodiazepine receptor and glucocorticoid synthesis by Ginkgo biloba extract EGb 761 and isolated ginkgolides.

Abstract: Glucocorticoid excess has broad pathogenic potential including neurotoxicity, neuroendangerment, and immunosuppression. Glucocorticoid synthesis is regulated by ACTH, which acts by accelerating the transport of the precursor cholesterol to the mitochondria where steroidogenesis begins. Ginkgo biloba is one of the most ancient trees, and extracts from its leaves have been used in traditional medicine. A standardized extract of Ginkgo biloba leaves, termed EGb 761 (EGb), has been shown to have neuroprotective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 0 publications
1
61
0
3
Order By: Relevance
“…[29][30][31] The cellular mechanisms underlying these multiple effects can be attributed to different components in the extract, which may act independently or synergistically. Although some of the cellular mechanisms have been found to involve terpenes such as ginkgolides or bilobalide, 32,33) many remain unexplained, despite the large number of experiments performed on these materials. Moreover, the anti-inflammatory effects of the water soluble portion of EGb 761 on inflammation caused by Candida albicans revealed that the terpene, rather than the flavone portion of this material is responsible for these therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] The cellular mechanisms underlying these multiple effects can be attributed to different components in the extract, which may act independently or synergistically. Although some of the cellular mechanisms have been found to involve terpenes such as ginkgolides or bilobalide, 32,33) many remain unexplained, despite the large number of experiments performed on these materials. Moreover, the anti-inflammatory effects of the water soluble portion of EGb 761 on inflammation caused by Candida albicans revealed that the terpene, rather than the flavone portion of this material is responsible for these therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were sacrificed 24 h later. Corticosterone was measured in organic extracts (ethyl acetate/ether, 1:1, v/v) of the collected sera by radioimmunoassay (Amri et al, 1996) under conditions suggested by the supplier of the antisera, ICN Diagnostics Division (Orangeburg, NY).…”
Section: Methodsmentioning
confidence: 99%
“…MA-10 mouse Leydig tumor cells were cultured in DMEM/F-12 medium supplemented with 5% FBS and 2.5% horse serum under 4% CO 2 (Brown et al, 1992). Human adrenal tumor H295R cells were maintained in DMEM/F-12 with 1% ITS ϩ [insulin (1 g/ml), transferrin (1 g/ml), selenium (1 g/ml), linoleic acid (1 g/ml), and bovine serum albumin (1.25 mg/ml)], 2.5% Nuserum, and 1% penicillin-streptomycin at 37°C, 6% CO 2 (Amri et al, 1996). Hepa1-6 mouse hepatoma cells were cultured in DMEM supplemented with 10% FBS and UT-1 cells were cultured in DMEM/F-12 medium supplemented with 8% fetal bovine lipoprotein-deficient serum and 2% FBS plus 40 M Compactin (Chin et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One component in EGb 761 is that the flavonoids have protective effects on cell membranes against destructive effects of free radicals and lipid peroxidation (2). Another important group found in EGb 761, the terpenoids, exhibit significant antioxidant activity (8) and regulate some mitochondria enzyme properties (1). The number of components in EGb 761 is over 60.…”
Section: Discussionmentioning
confidence: 99%